2020
DOI: 10.3390/polym12081664
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Nanochitin from Marine Resources and Fabrication of Polymer Nanocomposites: Recent Advances

Abstract: Industrial sea food residues, mainly crab and shrimp shells, are considered to be the most promising and abundant source of chitin. In-depth understanding of the biological properties of chitin and scientific advancements in the field of nanotechnology have enabled the development of high-performance chitin nanomaterials. Nanoscale chitin is of great economic value as an efficient functional and reinforcement material for a wide range of applications ranging from water purification to tissue engineering. The u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 129 publications
0
27
0
Order By: Relevance
“…Nanofibrillated chitin gels obtained in an acidic aqueous solution (pH 3) offer a unique possibility to process chitin-based materials in different forms and shapes for different applications. For instance, it can be used as reinforced material for biocomposite preparation [ 41 ] and it can be readily processed into films, hydrogels, or aerogels [ 8 , 16 , 42 ]. In the present work, the preparation and characterization of nanofibrillated chitin films are presented ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nanofibrillated chitin gels obtained in an acidic aqueous solution (pH 3) offer a unique possibility to process chitin-based materials in different forms and shapes for different applications. For instance, it can be used as reinforced material for biocomposite preparation [ 41 ] and it can be readily processed into films, hydrogels, or aerogels [ 8 , 16 , 42 ]. In the present work, the preparation and characterization of nanofibrillated chitin films are presented ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…This choice was derived from previous studies reporting on a viscosity mismatch between the two components in the melt, in particular using PLA [ 24 , 37 , 38 ]. In general, a number of CN/polymer nanocomposites, produced and processed from the molten state, have revealed improved mechanical properties along with anti-inflammatory and antimicrobial activity [ 24 , 39 , 40 , 41 ]. Some studies have reported on the feasibility of electrospinning CN/polymer nanocomposites, for example using CN/chitosan or CN/PCL solutions [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al synthesized a copolymer of poly (l-lysine) with ChS and studied its efficiency in relation to plasmid DNA adherence capability and gene transfection effect [ 85 ]. Rizeq et al [ 86 ] and Joseph et al [ 6 ] have extensively reviewed the various biomedical applications of ChS NPs.…”
Section: Chitin and Chitosan Nanomaterialsmentioning
confidence: 99%
“…Polymers of natural origins have been extensively employed not only in the food industry but also in pharmaceuticals [ 6 ]. Chitin, chitosan, alginate, and carrageenan are the most commonly used polysaccharide polymers in various pharmaceutical applications [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ] and food quality, safety, and preservation.…”
Section: Introductionmentioning
confidence: 99%